Analisa ketersediaan air DAS Siak untuk kebutuhan air PDAM Tirta Siak Pekanbaru - Joleha Joleha; Imam Suprayogi; Bochari Bochari; Vernando Sahputra Limbong (Jurnal Zona, 2022)
The availability of water from a water source needs to be known so that it can be used as needed. The main use of river water is as raw water whose management is carried out by a Regional Drinking Water Company (PDAM), which is a Regional Owned Enterprise (BUMD) which is engaged in drinking water services. The obstacle that is always experienced by PDAM users is that the service has not been maximized, both in quality and quantity. The purpose of this study was to determine the availability of water from the Siak watershed as a water source for PDAM Tirta Siak in order to meet the clean water needs of the people of Pekanbaru city. The stage of this research is to collect secondary data in the form of rainfall data and climatological data as well as a map of the Siak watershed. Data analysis was carried out by calculating 90% reliable discharge for raw water sources, calculating the clean water needs of the people of Pekanbaru city based on city categories for the population in 2021. The results of calculating the availability of the Siak watershed of 90% reliable flow were obtained at 12.65 m3/s. While the results of the calculation of the clean water needs of the people of Pekanbaru City for residents in 2021 are 1.73 m3/s. Compared to the production capacity of PDAM Tirta Siak which is only 0.08 m3/s, the amount of water available from the Siak Watershed is much larger than the current production capacity requirement of PDAM Tirta Siak.